Uncovering Ableism in Martha Fineman’s Ontological Vulnerability and Resilience Theory: A Critical Disability Theory Perspective - Arsenault-Gallant, Hannah (Critical Disability Discourses, 2025)
This paper begins with the premise that language contributes to the concept of disability and then engages a Critical Disability Theory (CDT) approach to scrutinize the rhetoric and language used by Martha Fineman in her work on ontological vulnerability and resilience. This paper will demonstrate that because the language used in Fineman’s ontological vulnerability theory and resilience model are highly susceptible to an ableist interpretation, her work inadvertently reinforces the notion that non-disabled people are fully human, while those with disabilities are insufficiently human. As a result, her scholarship may contribute to the prolonged oppression and othering of people with disabilities. The first part of the paper explains what CDT is, focusing largely on how ableism produces and sustains the co-constitutional concepts of disability and ability, and how CDT can be used as an approach for probing Fineman’s scholarship. The second part introduces ontological vulnerability and resilience theories, with a particular focus on Fineman’s work. The third part applies a CDT approach to uncover how Fineman’s language and rhetoric concerning vulnerability and resilience contribute to the construction of disability and ability. Finally, I highlight potential ways CDT scholars may reframe ontological vulnerability theory to overcome this issue. Keywords: Critical Disability Theory (CDT), vulnerability theory, Resilience Theory, Critical Feminist Theory, Martha Fineman